Commentary—Thoughts on State Action: The “Government Function” and “Power Theory” Approaches - Jesse H. Choper (Washington University Law Quarterly, 1979)
I would like to make a series of observations (and develop a few) that I hope will advance, rather than further confuse, analysis of "state action."
Keywords: Private schools; Private clubs; Equality; Welfare Rights